Detection of Mycobacterium bovis lymphocyte stimulating antigens in culture filtrates of a recombinant Mycobacterium smegmatis cosmid library - Gormley, E.; Fray, L.; Sandall, L.; Ke, G.; Dupont, C.; Carpenter, E. (Elsevier, 1999)
Culture filtrates derived from a Mycobacterium bovis cosmid library in Mycobacterium smegmatis were screened for bovine lymphocyte stimulatory antigens using peripheral blood mononuclear cells (PBMC) from cattle vaccinated with a low dose of Mycobacterium bovis BCG. Lymphocyte proliferation and interferon-gamma (IFN-?) production were used as cellular response markers for antigen recognition. In the primary screen, approximately 28% of all culture filtrates (CF) stimulated responses by PBMC from at least two out of four vaccinated cattle. In one of these CF, the M. bovis Ag85-B antigen was detected by Western-blot analysis. Despite heterogeneous lymphocyte responses of the animals, twenty-four of the culture filtrates stimulated lymphocyte proliferation and IFN-? production from at least six out of eight vaccinated animals in a secondary screen. Analysis of the cosmid DNA associated with these positive CF demonstrated that several contained homologous DNA sequences. It appears that the lymphocyte screening has detected M. bovis antigens that are immuno-dominant in cattle vaccinated with M. bovis BCG.